2012
DOI: 10.1083/jcb.201112015
|View full text |Cite
|
Sign up to set email alerts
|

PML promotes MHC class II gene expression by stabilizing the class II transactivator

Abstract: Promyelocytic leukemia (PML) protein binds to and stabilizes CIITA at PML nuclear bodies, which promotes expression of the MHC class II gene locus in response to interferon-γ exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 73 publications
4
60
0
Order By: Relevance
“…Recent evidence suggested a positive effect of PML on transcription of IFN-␥-stimulated genes and an involvement of one specific PML isoform in IFN-␤ production (44)(45)(46); however, the exact role of PML is far from being understood. To further characterize the influence of PML on interferon signaling, we measured ISG induction in HFFs with an shRNA-mediated depletion of PML (siPML) in comparison to that observed in control cells (siC).…”
Section: Effects Of Ie1 Mutants Ie1-l174p and Ie1 1-382 On The Inhibimentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggested a positive effect of PML on transcription of IFN-␥-stimulated genes and an involvement of one specific PML isoform in IFN-␤ production (44)(45)(46); however, the exact role of PML is far from being understood. To further characterize the influence of PML on interferon signaling, we measured ISG induction in HFFs with an shRNA-mediated depletion of PML (siPML) in comparison to that observed in control cells (siC).…”
Section: Effects Of Ie1 Mutants Ie1-l174p and Ie1 1-382 On The Inhibimentioning
confidence: 99%
“…This intermediate effect may arise from the low levels of IE1-L174P during infection. However, since PML recently emerged as a positive regulator of interferon signaling (44)(45)(46), it is also possible that the loss of PML binding caused by L174P mutation accounts for the inefficient suppression of the interferon response.…”
Section: Effects Of Ie1 Mutants Ie1-l174p and Ie1 1-382 On The Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of genomic sequences and genome-wide expression studies have revealed another form of nonrandom gene distribution, termed tandem gene arrays (TGAs), which represent contiguous stretches of gene loci that display differential regulation during cellular development and/or function (4,5). Importantly, gene clusters and TGAs also demonstrate expression-dependent nuclear localization patterns (6-9); therefore, gene loci are both deterministically arrayed along chromosomes and positioned within the nucleus (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…2E), the possibility that an IRIF/PML body association occurs randomly in the nucleus could not be fully excluded. We therefore employed a self-developed algorithm (48) to calculate the theoretical probability of association events between IRIF and PML bodies. This required determination of the number and volume of PML bodies and IRIF and the nuclear volume at several time points after irradiation (data not shown).…”
Section: Resultsmentioning
confidence: 99%